2022
DOI: 10.1177/26349817211065321
|View full text |Cite
|
Sign up to set email alerts
|

Best day since the bad germs came’: Exploring changing experiences in and the value of coastal blue space during the COVID-19 pandemic, a Fylde Coast case study

Abstract: Blue spaces have long been associated with beneficially impacting human health and wellbeing. This article reflects upon the impact of the COVID-19 pandemic on people’s experiences in coastal blue space and the health and wellbeing benefits derived from exposure to the space. Undertaken after the UK’s first lockdown during Summer 2020, the work employed a qualitative mixed methods approach through a survey and interviews to provide an in-depth case study of people’s experiences in and value of coastal blue spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Research across twenty European countries discovered that at the beginning of the pandemic, there was a significant increase in the number of online searches for topics relating to nature and the environment, which suggests an increased awareness or appreciation of nature at the population level [88]. During the initial phases of the pandemic, blue spaces were associated with providing stress relief and mental wellbeing at the individual level [89,90]. However, for many, access to blue spaces was restricted during the pandemic due to public health interventions; this, in turn, affected overall wellbeing levels and altered the therapeutic nature of these environments for individuals [91,92].…”
Section: Changing Perceptions At the Societal Levelmentioning
confidence: 99%
“…Research across twenty European countries discovered that at the beginning of the pandemic, there was a significant increase in the number of online searches for topics relating to nature and the environment, which suggests an increased awareness or appreciation of nature at the population level [88]. During the initial phases of the pandemic, blue spaces were associated with providing stress relief and mental wellbeing at the individual level [89,90]. However, for many, access to blue spaces was restricted during the pandemic due to public health interventions; this, in turn, affected overall wellbeing levels and altered the therapeutic nature of these environments for individuals [91,92].…”
Section: Changing Perceptions At the Societal Levelmentioning
confidence: 99%
“…An increase in health-related use of blue/ green spaces during lockdowns suggested that these spaces helped people cope with mental health stressors [25][26][27]. Populations sampled in the UK and Spain associated exposure to nature with mental health improvements and better sleep quality during the COVID-19 pandemic [28,29]; and fewer mental and physical symptoms suggest a bufering efect on the impacts of isolation [30][31][32][33]. Large proportions of blue/green spaces were also attributed to lower COVID-19-related cases and deaths in Poland [34].…”
Section: Introductionmentioning
confidence: 99%
“…Further, studies on coastal environments in relation to COVID-19, found the coast made people feel happy and peaceful before COVID-19, but these positive associations decreased as spaces became crowded and risk to physical health (i.e. probability of infection) increased (Earl et al, 2022). Interview data of coastal residents during COVID-19 lockdowns revealed a fragmented sense of home during lockdowns due to the inability to visit the coast, and this lack of attachment had a detrimental impact on their overall wellbeing (Jellard & Bell, 2021).…”
Section: Frequency Of Visitationmentioning
confidence: 99%